Fentanyl-Induced Respiratory Depression in an Intensive Care Unit Patient - Jayaram, Abhishek; Kumar, Gagana Ravi (Indian Journal of Pharmacy Practice)
Background: Fentanyl citrate, a potent opioid analgesic, is widely used for pain management in mechanically ventilated patients in WHO Adverse Drug Reaction Probability Scale (ICU). Its use, however, is associated with serious adverse reactions such as respiratory depression, particularly in patients with compromised respiratory systems. Case Presentation: We present a case of a 75-year-old male with Chronic Obstructive Respiratory Disease (COPD) and multifocal bronchopneumonia admitted to the ICU due to severe respiratory distress and hypoxia. Despite aggressive management including oxygen therapy, non-invasive ventilation, intubation, and mechanical ventilation, the patient’s condition deteriorated. Fentanyl citrate infusion was initiated for analgesia during mechanical ventilation. Unfortunately, this led to a progressive decline in oxygen saturation from 90% to 40% within 24 hr, indicating severe respiratory depression. Laboratory investigations revealed infection markers, and despite escalation of ventilatory support, the patient succumbed to acute respiratory failure. Discussion: This case highlights the critical importance of balancing effective pain management with the risk of respiratory depression in high-risk patients. Opioids like fentanyl, although effective for analgesia, pose significant risks in patients with pre-existing respiratory compromise. Alternative sedatives such as dexmedetomidine, ketamine, or remifentanil may offer safer options for pain management in such populations. Conclusion: The fatal outcome in this case underscores the need for individualized sedation strategies, vigilant monitoring, and careful selection of pharmacological agents to optimize outcomes in critically ill patients with respiratory compromise.
Keywords: Respiratory Depression; Adverse Drug Reaction; Fentanyl; Mechanical Ventilation; Fentanyl Citrate